Pengembangan Kurikulum Bahasa Arab Berbasis Karakter di MIN 1 Tulungagung - Siti Nur Azizeh; Ahmad Nurcholis; Budi Harianto; Ely Nur Khanifah; Syaikhu Ihsan Hidayatullah (LP3M Universitas Islam Zainul Hasan Genggong, 2020)
Arabic language has a very important role for Muslims, not only become the religious language (Al-Quran) but also a subject to be developed through curriculum development. Especially in developing the character-based curriculum where the children's moral is decline while the demands always grow. So, it is urgent to make the students’ quality by global standards. The research adjective is to describe how to develop the Arabic language curriculum in line with students’ character building. This is qualitative research that emphasizes the natural phenomenon of the object, that is the Arabic Curriculum Development at MIN 1 Tulungagung, the teacher role in applying the Arabic curriculum and carrying out the curriculum evaluation in the school. The efforts of curriculum development at MIN 1 Tulungagung are (1) Arabic-language routine activities, (2) Exemplary teachers and school staffs, and (3) Creating a good Arabic-speaking environment. The results of the study show that character-based Arabic curriculum development is carried out through: the integration of character values with Arabic subjects, self-development programs, building the values and ethics systems in schools, implementing the values and ethics in learning Arabic, applying various approaches, methods, and strategies.